IMITASI BUDAYA PADA TAYANGAN TELEVISI DI INDONESIA - Rizki Kurniawan (Jurnal Dimensi Seni Rupa dan Desain, 2014)
AbstractOne of the products from popular culture is television, there is no other media that can be compared with television in terms of volume of cultural texts produced and number of viewers. Currently the importance of television is the cultural and economic value, furthermore television is a form of democratic and creative culture as well. It instill in the minds of viewers that what is seen in the television seems to be ideal. As the main media of popular culture, television is the perfect distributor for it. Every time we are surrounded by popular culture, a culture that exist because we recognize its fame and fond of its existence.Audiences of popular culture imitate and follow trends, consume products associated with the image of the idol and trends, in order to associate themselves as a fans of popular culture icons they eventually being trapped to contribute to spread popular culture it self. AbstrakSalah satu produk dari budaya populer adalah televisi, tidak ada media lain yang bisa menyamai televisi dalam hal volume teks budaya yang diproduksi dan dalam hal jumlah penontonnya. Saat ini nilai penting dari televisi adalah nilai kultural dan ekonominya, selain juga merupakan bentuk budaya yang demokratis dan kreatif. Televisi menanamkan pengertian di benak khalayak pemirsanya , sebagai suatu yang ideal. Sebagai media utama budaya populer, televisi adalah penyalur yang sempurna untuk hal tersebut. Setiap saat kita di kelilingioleh budaya populer, budaya yang ada karena kita mengakuiketenarannya dan menggemari keberadaannya. Khalayak budaya populer mengimitasi dan mengikuti tren yang ada, mengkonsumsi produk yang berkaitan dengan citra idola dan tren tersebut, mengasosiasikan dirinya sebagai bagian dari penggemar ikon budaya populer tertentu yang pada akhirnya terjebak untuk berkontribusi untuk menyebarkan budaya populer itu sendiri.